UPAYA GURU BK DALAM MENGURANGI PERILAKU TERLAMBAT SISWA SMA MUHAMMADIYAH 7 SURABAYA - Layts Layyin; Budi Purwoko; Elisabeth Christiana (IKIP Siliwangi, 2026)
Meanwhile, late behavior itself includes deviant behavior, which includes behavior that goes out of the existing norms. In this study, researchers felt anxiety related to what efforts have been made by counseling teachers to reduce the late behavior of their students with the aim of reducing the late behavior of Muhammadiyah 7 Surabaya high school students. This research was conducted using a qualitative method with a phenomenological approach. For the stages themselves, researchers conducted school observations and then conducted interviews with the subjects and then analyzed the data obtained to draw conclusions from the data that had been obtained. Regarding the efforts that have been made by counseling teachers at SMA Muhammadiyah 7 Surabaya, counseling teachers have made various kinds of efforts, but it's just that they haven't found effective and appropriate provisions. Therefore, it is necessary for counseling teachers at SMA Muhammadiyah 7 Surabaya to try new and creative strategies to overcome the tardiness of students and students